Confirmation of G6.31+0.54 as a part of a Galactic supernova remnant. Issue 4 (28th June 2018) - Stupar, M; Parker, Q A; Frew, D J
ABSTRACT: A combination of archival multifrequency radio observations with narrow-band H α optical imagery and new confirmatory optical spectroscopy have shown that candidate supernova remnant (SNR) G6.31+0.54 can now be confirmed as part of a Galactic SNR. It has non-thermal emission, an optical emission line spectrum displaying shock excitation and standard SNR line ratios, fine filamentary structures in H α typical of optical remnants and closely overlapping radio and optical footprints. An X-ray ROSAT source 1RXS J175752.1–231105 was also found that matches the radio and optical emission though a definite association is not proven. Nevertheless, taken together, all these observed properties point to a clear SNR identification for this source. We provide a rough estimate for the kinematic distance to G6.31+0.54 of ∼4.5 kpc. The detected optical filaments are some ∼ 10 arcmin in extent (or about 13 pc at the assumed distance). However, as only a partial arcuate structure of the SNR can be seen (and not a full shell), the full angular extent of the SNR is unclear. Hence the physical extent of the observed partial shell is also difficult to estimate. If we assume an approximately circular shell then a conservative fit to the optical arc shaped filaments gives an angular diameter of ∼20 arcmin corresponding to a physical diameter of ∼26 pc that shows this to be an evolved remnant.